2018
DOI: 10.3390/jcm7010006
|View full text |Cite
|
Sign up to set email alerts
|

The Gut-Brain Axis and the Microbiome: Clues to Pathophysiology and Opportunities for Novel Management Strategies in Irritable Bowel Syndrome (IBS)

Abstract: Irritable bowel syndrome (IBS) is one of the most common of all medical disorders worldwide and, while for some it represents no more than a nuisance, for others it imposes significant negative impacts on daily life and activities. IBS is a heterogeneous disorder and may well have a number of causes which may lie anywhere from the external environment to the contents of the gut lumen and from the enteric neuromuscular apparatus and the gut immune system to the central nervous system. Consequently, the paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 51 publications
1
62
0
3
Order By: Relevance
“…IBS is a complex heterogeneous condition with a multifactorial pathogenesis. Proposed mechanisms involved in the pathogenesis of IBS include visceral hypersensitivity, gut-brain axis alterations, disorders in the epithelial barrier integrity leading to abnormal mucosal intestinal permeability, changed intestinal motility, immune system activation, food intolerance, low-grade inflammation, altered enteroendocrine pathways signaling, genetic basis (e.g., mutation in the SC5NA gene encoding a sodium channel ion; a number of single-nucleotide polymorphism studies have also identified polymorphisms in genes associated with IBS pathogenesis including genes coding for serotonin signaling, immune regulation, and epithelial barrier function), and the evolving concept of dysbiosis in the gut microbiota ( Figure 1) [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…IBS is a complex heterogeneous condition with a multifactorial pathogenesis. Proposed mechanisms involved in the pathogenesis of IBS include visceral hypersensitivity, gut-brain axis alterations, disorders in the epithelial barrier integrity leading to abnormal mucosal intestinal permeability, changed intestinal motility, immune system activation, food intolerance, low-grade inflammation, altered enteroendocrine pathways signaling, genetic basis (e.g., mutation in the SC5NA gene encoding a sodium channel ion; a number of single-nucleotide polymorphism studies have also identified polymorphisms in genes associated with IBS pathogenesis including genes coding for serotonin signaling, immune regulation, and epithelial barrier function), and the evolving concept of dysbiosis in the gut microbiota ( Figure 1) [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This concept is supported by the decreased concentrations of fecal unconjugated bile acids known to stimulate colonic secretion (deoxycholate and chenodeoxycholate) in IBS-C 123 . Regarding the role of the microbiome-gut-brain axis in IBS (reviewed in 124 and 125 ), probiotic therapy has been shown to modulate CNS function in healthy volunteers 126 through effects on brain regions controlling processing of emotion and sensation. More recently, in a recent placebo controlled trial in IBS patients, treatment with the probiotic B. longum NCC3001 was associated with improved symptoms of depression and changes in brain activation patterns measured by functional magnetic resonance imaging 127 .…”
Section: Functional Gi Disordersmentioning
confidence: 99%
“…Ezzo [83] Case Though research still has not definitively proven the cause of IBS, recent scientific and clinical studies point to an organic etiology linking abdominal pain to a braingut connection [29,30,86] and to the changing luminal environment within the bowel leading to changes in stool form [87][88][89].…”
Section: Ibs-related Clinical Research Experience With Belladonna Alkmentioning
confidence: 99%